2018
DOI: 10.1016/j.invent.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the implementation of an internet intervention in well-baby clinics: A pilot study

Abstract: PurposeDespite promising results, internet interventions are not widely accessible or well-integrated in health services. The objective of this study was, therefore, to examine the implementation of an internet intervention (‘Mamma Mia’) for the prevention of perinatal depression in Norwegian well-baby clinics (i.e., primary care).MethodsMamma Mia begins in mid-pregnancy and lasts up to 6 months after childbirth. It consists of 44 online sessions, supported by midwives and public health nurses at up to 5 conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…However, child and youth mental health workers seem cautiously positive [ 23 , 24 ], particularly in the prevention and treatment of mild-to-moderate mental health problems [ 24 , 25 ]. Furthermore, previous research has shown that leadership and different leadership styles may also have an impact on the adoption and perceived usefulness of technology [ 26 , 27 ]. Thus, it is necessary to consider perceived usefulness from the perspective of different professions/health care services for young children and professional roles (eg, practitioners vs leaders), which, to the best of our knowledge, has not been previously studied directly.…”
Section: Introductionmentioning
confidence: 99%
“…However, child and youth mental health workers seem cautiously positive [ 23 , 24 ], particularly in the prevention and treatment of mild-to-moderate mental health problems [ 24 , 25 ]. Furthermore, previous research has shown that leadership and different leadership styles may also have an impact on the adoption and perceived usefulness of technology [ 26 , 27 ]. Thus, it is necessary to consider perceived usefulness from the perspective of different professions/health care services for young children and professional roles (eg, practitioners vs leaders), which, to the best of our knowledge, has not been previously studied directly.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite this, in therapists’ everyday practice, unresolved priority issues formed organisational barriers to the programme’s implementation. Previous studies have highlighted competing demands to the ICBT treatments, especially regarding available time for the therapists to engage in ICBT treatments [ 22 , 26 28 ], implying that therapists need protected time for ICBT-i. This barrier also indicates that implementing ICBT in clinics or organisations with a wider health care assignment requires other strategies than in specific ICBT clinics.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that implementation activities, such as therapist training and supervision, facilitated the implementation, is also supported by previous studies. Training regarding the evidence base for internet-delivered treatment has been shown to facilitate ICBT implementation [ 11 , 26 28 ], as well as practical training in the programme itself [ 26 ], supervision of therapists during the intervention [ 11 , 28 ], and technical support [ 25 ]. In a scale-up implementation it is important to meet the continuous need for training, supervision, and support of the ICBT therapists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One generalizable implementation framework that has been applied across disciplines is the AIF (Fixsen, Naoom, Blase, Friedman, & Wallace, ). In addition to demonstrating utility in human services, the evidence‐based AIF has been used in several studies within health care (Drozd, Haga, Lisoy, & Slinning, ; Drozd et al, ; Lala, ; Scovil et al, ). One intermediary organization, IIK, has worked to utilize implementation theory and principles from the AIF to support the high‐quality implementation, scale‐up, and sustainment of the NFP in Colorado.…”
Section: The Nurse–family Partnershipmentioning
confidence: 99%